Replication Data for: Semi-automatic Ice Rafted Debris quantification with Computed Tomography - van der Bilt, Willem Godert Maria (DataverseNO, 2021)
This dataset includes all analyses performed on the cores CT-scanned presented in Cederstrøm et al. 2021 – accepted in Paleoceanography and Paleoclimatology, but at the time of writing only accessible as a pre-print via https://www.essoar.org/doi/abs/10.1002/essoar.10506939.1. The data presented derive from two datasets. First, synthetic sediment archives (phantoms) that were spiked with approximately 25, 100, 500, 1000 and 2000 grains in the 150-500 µm fraction of different lithologies that are common in Ice Rafted Debris (IRD) source areas: basalt (B 0-4), dolomite (D 0-4), quartz (Q0-4), and a 1:1:1: mixture of each of the latter (M0-4). And secondly, sections of two natural sediment archives in which 150-500 µm sized IRD was counted at 2 cm intervals using standard manual protocols. Both of these cores, named GS16-204-22CC GS16-204-18CC, derive from East Greenland (Denmark Strait). The data are organized per paper figure per .txt file. The data behind Fig. 1 includes information on the composition (weight, number of grains per gram of dry sediment, number of foraminifera shells) of each synthetic sediment archive. The data behind Fig. 2 includes Mastersizer and CT-derived grain size distribution information (volume percentage per size fraction) for each of the lithologies used to spike each synthetic sediment archives. The data behind Fig. 3 includes manually ascertained and CT-derived particle counts (number of grains per gram of dry sediment) for each of our synthetic sediment archives. Both counts include standard deviations (σ). For the manually ascertained numbers, these were based on quantified human counting errors. For CT-derived numbers, σ values were calculated from counts of two sample volumes (A and B). The data behind Fig. 4 includes manual and CT-derived 150-500 µm IRD counts for each of the scanned sections from cores GS16-204-22CC (454.25-488.25 cm) and GS16-204-18CC (232.25-280.25 cm) in grains per gram of dry sediment. This file also includes the 0.5 cm re-counts performed on the 267.25-280.25 cm interval of the scanned section from core GS16-204-18CC. Additional details can be found in the appended readme file.